2022
DOI: 10.1021/accountsmr.2c00078
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Tris-Heteroleptic Cyclometalated Phosphorescent Iridium(III) Complexes: An Emerging Class of Metallophosphors

Abstract: Metrics & MoreArticle Recommendations * sı Supporting Information CONSPECTUS:The rapid developments of cutting-edge research on photofunctional organic semiconductor materials are greatly promoting the progress of science and technology. As one of the most important organic semiconductor materials, phosphorescent iridium(III) complexes are a promising class of organometallic emitters because of their rich emissive excited states together with excellent chemical stability, which have been widely used in various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
44
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 56 publications
1
44
0
1
Order By: Relevance
“…2 Due to the spin-orbit coupling effect, heavy metal complexes can simultaneously harvest singlet and triplet excitons, leading to an internal quantum efficiency of up to 100%. 3,4 In particular, owing to their high photoluminescence quantum yields (PLQYs), short phosphorescence lifetimes, facile color adjustments and good stability, iridium(III) metal complexes are considered as one of the most promising lightemitting materials for practical applications. [5][6][7] However, there are still some thorny problems in the development of blue phosphorescent iridium(III) complexes with regard to color purity, stability and emission efficiency, as compared to green and red phosphorescent iridium(III) complexes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Due to the spin-orbit coupling effect, heavy metal complexes can simultaneously harvest singlet and triplet excitons, leading to an internal quantum efficiency of up to 100%. 3,4 In particular, owing to their high photoluminescence quantum yields (PLQYs), short phosphorescence lifetimes, facile color adjustments and good stability, iridium(III) metal complexes are considered as one of the most promising lightemitting materials for practical applications. [5][6][7] However, there are still some thorny problems in the development of blue phosphorescent iridium(III) complexes with regard to color purity, stability and emission efficiency, as compared to green and red phosphorescent iridium(III) complexes.…”
Section: Introductionmentioning
confidence: 99%
“…To increase the ligand-centered triplet state (i.e. 3 LC) energy by appropriate ligand modification, e.g. by adding a heteroatom in the C-coordinating ring of the cyclometalating ligands, was proved favorable to cause a hypsochromic shift of phosphorescence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 It was not until we developed the approach of reacting two different 2-phenylpyridine-based ligands (L a and L b ) with IrCl 3 ·3H 2 O to form a mixture of iridium chloro-bridged dimers followed by reaction with acetylacetone to give a statistical mixture of Ir(L a ) 2 (acac), Ir(L a )(L b )(acac), and Ir(L b ) 2 (acac) species that Ir(L a )(L b )(acac) complexes could be separated by chromatography. 10 12 Following this, new approaches have been developed that initially use the degradation of a tris -cyclometalated to a mixed ligand iridium-chloro dimer, which was coordinated to an ancillary ligand to form a tris -heteroleptic complex. 13 15 Adamovich et al recently reported an approach that used an aryl- N -heterocyclic carbene ligand to form an intermediate iridium complex that favored the formation of mixed ligand chloro dimers, avoiding statistical distributions of products.…”
mentioning
confidence: 99%
“…Despite bis -heteroleptic iridium complexes being well-established, there remain relatively few examples of tris -heteroleptic iridium complexes . It was not until we developed the approach of reacting two different 2-phenylpyridine-based ligands (L a and L b ) with IrCl 3 ·3H 2 O to form a mixture of iridium chloro-bridged dimers followed by reaction with acetylacetone to give a statistical mixture of Ir­(L a ) 2 (acac), Ir­(L a )­(L b )­(acac), and Ir­(L b ) 2 (acac) species that Ir­(L a )­(L b )­(acac) complexes could be separated by chromatography. Following this, new approaches have been developed that initially use the degradation of a tris -cyclometalated to a mixed ligand iridium-chloro dimer, which was coordinated to an ancillary ligand to form a tris -heteroleptic complex. Adamovich et al recently reported an approach that used an aryl- N -heterocyclic carbene ligand to form an intermediate iridium complex that favored the formation of mixed ligand chloro dimers, avoiding statistical distributions of products …”
mentioning
confidence: 99%